2011
DOI: 10.5535/arm.2011.35.4.548
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Conduction Study of the Superficial Peroneal Sensory Distal Branches in Koreans

Abstract: ObjectiveTo perform nerve conduction studies of the four branches of the superficial peroneal nerves to determine normal values and anatomic variations in Koreans.MethodAntidromic sensory nerve conduction studies of the four distal branches were performed on 70 healthy subjects (100 feet). We applied electrical stimulation at the midpoint of medial and lateral malleoli for the medial dorsal cutaneous nerve (MDCN), and at the lateral 1/4 point between the medial and lateral malleoli for the 2 branches of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…On the other hand, activation of p38 MAPK signaling pathway is essential for in vitro and in vivo IL-17 production, and is required for the development and progression of CNS proinflammatory demyelination [41]. p38 MAPK signaling has also been found to be involved in insufficient NSC proliferation; targeting p38 restored these cells and corrected neuromotor deficits in an ataxia-telangiectasia mouse model [42]. The importance of p38 MAPK activation in the inhibition of NSC proliferation has also been observed by culturing NSCs with IL-1β, another proinflammatory cytokine that is involved in CNS proinflammatory demyelination [43].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, activation of p38 MAPK signaling pathway is essential for in vitro and in vivo IL-17 production, and is required for the development and progression of CNS proinflammatory demyelination [41]. p38 MAPK signaling has also been found to be involved in insufficient NSC proliferation; targeting p38 restored these cells and corrected neuromotor deficits in an ataxia-telangiectasia mouse model [42]. The importance of p38 MAPK activation in the inhibition of NSC proliferation has also been observed by culturing NSCs with IL-1β, another proinflammatory cytokine that is involved in CNS proinflammatory demyelination [43].…”
Section: Discussionmentioning
confidence: 99%
“…It is also subjected to biopsy (Ruth et al, 2005) or nerve conducting studies for the diagnosis of diseases such as diabetic neuropathy (Kwon et al, 2000). Thus, it is necessary to understand the formation and distribution of the sural nerve, for better clinical performance such as the operation design of related areas (Aktan Ikiz et al, 2005) and location of correct test points (Kim et al, 2003;Ko et al, 2011). Likewise, nerve entrapment occasionally occurs at the site (Pringle et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, nerve entrapment occasionally occurs at the site (Pringle et al, 1974). Thus, it is necessary to understand the formation and distribution of the sural nerve, for better clinical performance such as the operation design of related areas (Aktan Ikiz et al, 2005) and location of correct test points (Kim et al, 2003;Ko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are various possible reasons for the discrepancy in results of studies. Ko et al . reported that racial difference may be a strong factor.…”
Section: Discussionmentioning
confidence: 99%
“…Their results were similar to those obtained by Izzo et al ., who showed that an IDCN SNAP was absent in only 2% of subjects. However, Ko et al . reported that anatomical variations were present in 66% of the IDCNs in Koreans.…”
mentioning
confidence: 98%